2019
DOI: 10.1016/j.jcf.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The main mechanism associated with progression of glucose intolerance in older patients with cystic fibrosis is insulin resistance and not reduced insulin secretion capacity

Abstract: Background: Aging cystic fibrosis (CF) patients are at high risk of developing CF-related diabetes (CFRD). Decrease in insulin secretion over time is the main hypothesis to explain this increasing prevalence but mechanisms are still not well elucidated. The objective is to assess evolution of glucose tolerance and insulin secretion/sensitivity in aging CF patients. Methods: This is a retro-prospective observational analysis in the older adult CF patients from the Montreal Cystic Fibrosis Cohort (n = 46; at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 41 publications
0
28
0
3
Order By: Relevance
“…Последние исследования показывают, что ген CFTR непосредственно не регулирует секрецию инсулина или глюкагона, и в основном МЗСД вызван повреждением поджелудочной железы хроническим воспалением, фиброзом, дисфункцией и гибелью β-клеток в условиях прогрессирующего полиорганного заболевания, при котором поражение экзокринной функции поджелудочной железы наблюдается с рождения у около 85 % пациентов [6]. В нескольких исследованиях анализировалась взаимосвязь фенотипов, обусловленных МВ заболеваний поджелудочной железы, с вариантами гена CFTR [7][8][9]. Показано, что нарушения метаболизма глюкозы являются частым коморбидным состоянием у пациентов, которые имеют генетический вариант c.1521_1523delCTT (p.Phe508del, F508del) [9,10].…”
Section: муковисцидоз Original Researchunclassified
See 1 more Smart Citation
“…Последние исследования показывают, что ген CFTR непосредственно не регулирует секрецию инсулина или глюкагона, и в основном МЗСД вызван повреждением поджелудочной железы хроническим воспалением, фиброзом, дисфункцией и гибелью β-клеток в условиях прогрессирующего полиорганного заболевания, при котором поражение экзокринной функции поджелудочной железы наблюдается с рождения у около 85 % пациентов [6]. В нескольких исследованиях анализировалась взаимосвязь фенотипов, обусловленных МВ заболеваний поджелудочной железы, с вариантами гена CFTR [7][8][9]. Показано, что нарушения метаболизма глюкозы являются частым коморбидным состоянием у пациентов, которые имеют генетический вариант c.1521_1523delCTT (p.Phe508del, F508del) [9,10].…”
Section: муковисцидоз Original Researchunclassified
“…В нескольких исследованиях анализировалась взаимосвязь фенотипов, обусловленных МВ заболеваний поджелудочной железы, с вариантами гена CFTR [7][8][9]. Показано, что нарушения метаболизма глюкозы являются частым коморбидным состоянием у пациентов, которые имеют генетический вариант c.1521_1523delCTT (p.Phe508del, F508del) [9,10].…”
Section: муковисцидоз Original Researchunclassified
“…Scheuing et al carefully delineated insulin doses in CFRD compared with T1DM and found that those with CFRD needed more [20]. Although there is increasing literature that insulin sensitivity declines as the CF population ages [24], it is still recommended to initiate insulin at lower doses and then adjust based on the patient's response. Insulin dosing needs in CFRD typically average <0.5À0.8 units/kg/ day, and typically do not differ between adolescents and adults [25].…”
Section: Cfrdmentioning
confidence: 99%
“…The role of insulin resistance is currently debated, but there is evidence to suggest its contribution to the development of dysglycemia in CF patients, particularly in certain states, such as the use of steroids and acute pulmonary infections [11, 14]. Furthermore, it has been shown that in the context of low insulin secretion, insulin resistance can modulate glucose tolerance changes over time [15, 16] and in response to exercise [17].…”
Section: Introductionmentioning
confidence: 99%